Specialization and Persistence in the Arrest Histories of Sex Offenders. A Comparative Analysis of Alternative Measures and Offense Types - Miethe, Terance D. (Journal of research in crime and delinquency, 2006)
A basic assumption underlying current public policy and crime-control efforts is that sex offenders are highly specialized and persistent. Using national data on about 10,000 sex offenders released from prison in 1994, this study explored this assumption by comparing the arrest patterns and cycles of sex offenders and other offenders. As a group and across various measures, sex offenders had low levels of specialization and persistence in offending in absolute and relative terms. Similar conclusions were reached when specific types of sex offenders (e.g., rapists, child molesters) were compared with other particular offenders (e.g., robbers, burglars, drug offenders), but the results were more measure dependent. Even among persistent serial sex offenders, rapists and child molesters were found to specialize only within a more predominant pattern of versatility across their criminal careers. These results are discussed in terms of their implications for future research and current public policy that are predicated on assumed specialization and persistence among sex offenders